Investigate the potential of using reactor anti-neutrinos for nuclear safeguards in Vietnam - Cao, Son; Tran, Ngoc; Nguyen, Van; Phan, Quyen (Communications in Physics, 2023)
One of the most abundant man-made sources of low energy (few MeVs) neutrinos, reactor neutrino, is not only useful for studying neutrino properties, but it is also used in practical applications. In this study, we investigate the potential of using reactor neutrino detectors for nuclear safeguards in Vietnam, specifically at the Dalat Nuclear Reactor, a future research facility, and presumably commercial reactors with 500 kW, 10 MW, and 1000 MW thermal powers, respectively. We compute the rate of observed inverted beta decay events, as well as the statistical significance of extracting isotope composition under the practical assumptions of detector mass, detection efficiency, and background level. We find that a 1-ton detector mass can allow us to detect the reactor’s on-off transition state from a few hours to a few days, depending on the standoff distance and reactor thermal power. We investigate how background and energy resolution affect the precision of the extracted weapon-usable \(^239\)Pu isotope. We conclude that in order to distinguish the 10% variation of the \(^239\)Pu in the 10 MW thermal power reactor, a 1-ton detector placed 50 m away must achieve 1% background level. Increasing the statistics by using a 10x larger detector or placing it \(10\) times closer to the reactor alleviates the requirement of the background level to 10%.